2007
DOI: 10.1161/circulationaha.106.680231
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Oxide Labeling and Outcome of Transplanted Mesenchymal Stem Cells in the Infarcted Myocardium

Abstract: Background-Cell labeling with superparamagnetic iron oxide (SPIO) nanoparticles enables noninvasive MRI and tracking of transplanted stem cells. We sought to determine whether mesenchymal stem cell (MSC) outcome is affected by SPIO labeling in a rat model of myocardial infarction. Methods and Results-Rat MSCs were labeled with SPIO (ferumoxides; Endorem; Guerbet, Villepinte, France). By trypan-blue exclusion assay, almost 100% of the cells remained viable after labeling. Seven days after MI, rats were randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
296
5
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 295 publications
(313 citation statements)
references
References 34 publications
11
296
5
1
Order By: Relevance
“…Previous studies showed that this could pose a problem and demonstrated up to 100% phagocytosis of the transplanted MSCs, injected into a myocardial infarct scar [52]. Moreover, a recent study has claimed that rat-derived MSCs cannot survive more than 14 days, even in a naïve rat brain [53].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that this could pose a problem and demonstrated up to 100% phagocytosis of the transplanted MSCs, injected into a myocardial infarct scar [52]. Moreover, a recent study has claimed that rat-derived MSCs cannot survive more than 14 days, even in a naïve rat brain [53].…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of i.v. injected PS-presenting liposomes by cardiac macrophages was investigated in a rat model of acute MI (23). Forty-eight h after MI, the SD rats were injected through the femoral vein with 0.03 M of PS-presenting liposomes containing iron oxide (2 μg∕mL) (n ¼ 4) or saline as a control (n ¼ 4).…”
Section: Induction Of Myocardial Infarction (Mi)mentioning
confidence: 99%
“…These agents have no negative effects on cell viability, proliferation or differentiation [81,82] . The toxicity of iron oxide particles is less than free gadolinium because free iron particles released from dead iron MR contrast media can be introduced into the intracellular compartments by endocytosis, phagocytosis or magnetoelectroporation.…”
Section: Cell Labelingmentioning
confidence: 99%